Discrete element simulation of surface mechanical attrition treatment with rough-surface sonotrode. (October 2019) - Zhang, Yongmei; Proust, Gwénaëlle; Retraint, Delphine; Wang, Huamiao; Gan, Yixiang
Highlights: A DEM model for SMAT with rough-surface sonotrode is built. The impact statistics are connected to the surface characteristics. Impact statistics have correlations with processing parameters and sensitive parameters have been found. Mechanistic models for predicting impact angle and velocity distributions are proposed for process optimization. Abstract: Surface mechanical attrition treatment (SMAT) is a specialized cold working method that is used to induce compressive residual stresses and refine crystalline grains at the surface of metal components. This technique is increasingly employed in different industries, and the control and optimization of the method require fundamental understanding and accurate process modelling, in particularly detailed information regarding the shot-target interaction. This paper presents a Discrete Element Method (DEM) study of the shot dynamics with rough sonotrodes. These rough surfaces are created by grouping in a hexagonal packing of identical spheres. Different roughness values are obtained by varying the sphere diameter and spacing. The coefficient of restitution (CoR) between shot and target used in our DEM simulations was obtained from Finite Element Method (FEM) simulations of multiple shot-target impacts. The DEM results are analyzed after the SMAT process has reached the steady state. The relationships between surface roughness and the resulting impact angle and velocity distributions are investigated. Furthermore, based on a parametric study, we conducted correlation analyses between processing parameters and shot dynamics, and identified key conditions, using the mechanistic models. The proposed numerical method and findings of this study could be used to tailor the SMAT processes.